Could the North American opioid crisis hit Switzerland? - Jean-Baptiste Armengaud; Carole-Anne Baud; Stéphanie Beuriot; Barbara Broers; Jennifer Hasselgard-Rowe; Valérie Junod; Bengt Kayser; Victor Leroy; Sophie Pautex; Caroline Schmitt-Koopmann; Olivier Simon; Elodie Wehrli (Swiss Medical Weekly)
No abstract available.